Delayed cord clamping for prevention of iron deficiency anemia in term infants - Olga Rasiyanti Siregar; Bugis Lubis; Muara Lubis; Bidasari Lubis; Guslihan Dasa Tjipta (Indonesian Pediatric Society, 2012)
Background Iron deficiency childhood is a concern due to its potentially detrimental effectson development, some of which may be irreversible even after irontreatment. Delayed cord clamping may prevent IDA by increasingan infant's iron reserve at birth.Objective We aimed to evaluate the effect of delayed umbilicalcord clamping at birth on the iron status in newborns at age 24hours of life.Methods This randomized, singleô€’blind study was conducted fromMarch to May 2009, at two general hospitals in Medan, NorthSumatera Province. Eligible newborn infants were randomlyassigned to one of two groups: early cord clamping (Eee)performed 15 seconds after delivery or delayed cord clamping(DeC) performed 2 minutes after delivery. Infants were placed ontheir mothers' abdomens before the umbilical cords were clamped.Hematologic status was determined from umbilical cord blood.Results Sixtyô€’three subjects were included in our study, consistingof31 infants in the Eee group and 32 infants in the Dec group.We found that mean neonatal hemoglobin level was higher inthe Dec group than in the Eee group ( 18.4 g% and 16.2 g%,respectively, P=O.OOOl). Also, mean ferritin level was higher inthe Dec group than in the Eee group (556 mg/dL and 329 mg/dL, respectively, p=o.o 15). Other hematological status indicators,including mean hematocrit and mean corpuscular volume (MeV)level, were also higher in the Dec group. However, mean redblood cell levels were not significantly groups. Nor was there a significant level between the Dec and Eee groups.Concl usion Dela y ed cord c l a m p i n g m a y improve ironstatus and prevent IDA in term infants. [Paediatr Indones.2012;52:223-8].